Effect of adding the dry material of olive leaves on the productive parameters of broiler (Journal of Hama University, 2022)
The research was conducted on 120 birds of strain (ROSS 308) with a similar weight and age one day and unsexed in order to study the effect of different concentrations of the powder of the olive leaf on some productivity indicators in broilers such as feed consumption rate and live weight and feed conversion factor. were distributed birds randomly into four groups of 30 birds each group and each group containing three  replicates and were given a standard diet to the first group (control), while dry matter was added to the olive leaf concentrations (1-2-3) %/ kg respectively to a standard diet, the experiment lasted for 42 days. The results of the experiment showed that the addition of olive leaf for the standard diet for broiler led to an increase significantly (P
Keywords: olive leaves, broiler, productive parameters , feed consumption